One step forward and many to the side: Combating gender violence in Afghanistan, 2001–2014. (July 2015) - Wimpelmann, Torunn
Synopsis: This article offers some reflections on the efforts over the last decade to combat violence against women in Afghanistan through reforms of laws and the justice system. The paper identifies two intersecting factors that have curtailed the transformative impact of these efforts. First, law making and legal practices have become infused with various forms of personalized and hierarchical politics. Progressive laws have taken the form of gifts bestowed to women by the president (and NATO countries) rather than gains achieved through broader political mobilization. Furthermore, the widespread application of 'mediation' in cases of gender violence serves to defuse claims of justice and instead leave women dependent on the benevolence of self-appointed patrons. Second, existing sexual ideologies have rarely been challenged, with women routinely arrested and prosecuted for 'escaping' from home or for 'attempted' adultery. The overall result is a 'protect and rescue' approach to gender violence that does little to transform the underlying causes of women's subordination.